Matrix - Groff, Lauren (New York : Riverhead Books, 2021)
Cast out of the royal court, 17-year-old Marie de France, born the last in a long line of women warriors, is sent to England to be the new prioress of an impoverished abbey where she vows to chart a bold new course for the women she now leads and protects.
Keywords: Marie, de France -- active 12th century -- Fiction; Nuns -- Fiction; Faith -- Fiction; Divine visions -- Fiction; Historical fiction